Application of Ant Algorithm for Software Optimization - Mahmudova, Shafagat (Review of Information Engineering and Applications, 2020)
Different technologies, methods and algorithms are used when developing high-quality software systems. There are various ways to create optimal software. One of them is an ant algorithm. The ant algorithm can be attributed to the field of biomimetic. Ant algorithm is one of the most effective polynomial algorithms for finding approximate solutions, and it also solves similar route search problems in graphs. Various methods, including the ant algorithm, are used to improve software efficiency and optimize it. The essence of the concept is to analyze, use, and meta-heuristically optimize the behavior of ants in search of paths to the food source of the colony. This article analyzes the studies in this area, and explains the idea of the algorithm used, compares different ant systems, shows program code operators as ants, and applies the ant algorithm to them. As a result of applying the algorithm, the shortest path to some operators (cycle, condition) contained in the program code is found. The experiments perform good results.